2012
DOI: 10.1111/j.1471-4159.2012.07700.x
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotides released from Aβ1–42‐treated microglial cells increase cell migration and Aβ1–42 uptake through P2Y2 receptor activation

Abstract: Amyloid β-protein (Aβ) deposits in brains of Alzheimer’s disease (AD) patients generate proinflammatory cytokines and chemokines that recruit microglial cells to phagocytose Aβ. Nucleotides released from apoptotic cells activate P2Y2 receptors (P2Y2Rs) in macrophages to promote clearance of dead cells. In this study, we investigated the role of P2Y2Rs in the phagocytosis and clearance of Aβ. Treatment of mouse primary microglial cells with fibrillar (fAβ1–42) and oligomeric (oAβ1–42)Aβ1–42 aggregation solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
74
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(76 citation statements)
references
References 64 publications
2
74
0
Order By: Relevance
“…It has been reported that following injury or neuroinflammation, P2Y 6 Rs are functionally upregulated in microglial cells and their activation by UDP triggers phagocytosis [144]. Our data with mouse primary microglial cells indicate that P2Y 2 R activation enhances microglial cell migration (Table 1) and their uptake and degradation of neurotoxic oligomeric Aβ 1-42 ( Table 2), responses that were markedly decreased in microglia from P2Y 2 R −/− cells [145].…”
Section: P2y 2 Receptors In Glial Cellssupporting
confidence: 52%
See 1 more Smart Citation
“…It has been reported that following injury or neuroinflammation, P2Y 6 Rs are functionally upregulated in microglial cells and their activation by UDP triggers phagocytosis [144]. Our data with mouse primary microglial cells indicate that P2Y 2 R activation enhances microglial cell migration (Table 1) and their uptake and degradation of neurotoxic oligomeric Aβ 1-42 ( Table 2), responses that were markedly decreased in microglia from P2Y 2 R −/− cells [145].…”
Section: P2y 2 Receptors In Glial Cellssupporting
confidence: 52%
“…Although the endogenous expression of P2Y 2 Rs has been reported in mouse microglia [67,214], it seems likely that increased levels of proinflammatory cytokines should further increase P2Y 2 R expression in glial cells in vivo. Our recent in vitro data show that treatment of mouse primary oligomeric/oligomeric Aβ 1-42 upregulates P2Y 2 R expression [145] via a pathway likely involving P2X7R-mediated IL-1β release [16,75,105,[154][155][156]. It also has been determined that P2X7R activation increases P2Y 2 R expression in rat astrocytes [215].…”
Section: P2y 2 Rs In Cns Inflammationmentioning
confidence: 95%
“…4). Our group has previously shown that the P2Y 2 R contains an RGD motif in its first extracellular loop that enables receptor interaction with RGDbinding ␣ V ␤ 3/5 integrins to stimulate cell migration (6,26,64,117). However, P2Y 2 R interactions with other RGD-binding integrins have not been previously reported.…”
Section: Discussionmentioning
confidence: 99%
“…These nucleotides also promote the processing of the amyloid precursor protein. In addition, β-amyloid upregulates P2Y 2 R in microglial cells, which enhances phagocytosis and degradation of β-amyloid (Kim et al, 2012). Thus, P2Y 2 R expression in neurons and microglial cells under pro-inflammatory and pro-apoptotic conditions might prevent neurodegeneration.…”
Section: Discussionmentioning
confidence: 99%